IMPLEMENTASI PROGRAM ASI EKSKLUSIF DI PUSKESMAS ALAI KECAMATAN TEBING TINGGI BARAT KABUPATEN KEPULAUAN MERANTI TAHUN 2020 - Welly Sando; Dami Yanthi; Muhammad Dedi Widodo; Tengku Khairani (Universitas Pahlawan, 2020)
Implementation is the implementation of laws in which various actors, organizations, procedures, and techniques work together to carry out policies in an effort to achieve policy objectives or policy programs. Exclusive breastfeeding coverage The Meranti Islands District Health Office experienced the lowest exclusive breastfeeding coverage in 2019, namely Alai Community Health Center, which is 25% where the achievement of the exclusive Breastfeeding Program (ASI) in Meranti Islands Regency in 2019 is 50% and still far from the national target of 80%. This study aims to determine the implementation of the exclusive breastfeeding program at Alai Public Health Center, Tebing Tinggi Barat District, Meranti Islands Regency in 2020. This type of qualitative research uses observational research. When the research was conducted in June-August at the Alai Public Health Center, Tebing Tinggi Barat District, Meranti Islands Regency. The research subjects were the head of the puskesmas (IK1), pregnant women (IU1), PJ KIA (IP1), and posyandu cadres (IP2). Data analysis is used by systematically arranging the interview guidelines, then processing the data, data from observations are identified to describe each variable, a summary will be presented in narrative form. The results of this study indicate that the policies in the exclusive breastfeeding program have been implemented but the coverage of exclusive breastfeeding is still low because many pregnant women do not follow the recommendations that have been given by health workers in counseling such as the benefits of breastfeeding. It can be concluded that health workers in the policy of the exclusive breastfeeding program provide counseling to pregnant women and approach pregnant women in order to achieve an exclusive breastfeeding program. It is recommended that the head of the Alai Community